The Impact of GIP (Gastric Inhibitory Polypeptide) on the Development of Type 2 Diabetes in the Spanish Population: A Longitudinal Study - Isabella Alvarez; Daniel Perez (Sriwijaya Journal of Internal Medicine, 2024)
Introduction: Gastric inhibitory polypeptide (GIP) is an incretin hormone with a complex role in glucose homeostasis. While it stimulates insulin secretion, it has also been implicated in adiposity and potentially in the pathogenesis of type 2 diabetes mellitus (T2DM). This longitudinal study investigated the relationship between GIP levels and the development of T2DM in a Spanish cohort. Methods: We followed 1,200 non-diabetic Spanish adults (aged 40-65 years) for 10 years. Baseline measurements included anthropometric data, fasting GIP levels, oral glucose tolerance tests (OGTT), and lifestyle factors. Incident T2DM cases were identified through OGTT and medical records. Cox proportional hazard models were used to assess the association between GIP and T2DM risk, adjusting for potential confounders. Results: During the follow-up, 187 participants developed T2DM. Baseline GIP levels were significantly higher in individuals who developed T2DM compared to those who remained non-diabetic (p<0.001). After adjusting for age, gender, BMI, family history of diabetes, physical activity, and dietary habits, elevated GIP levels were independently associated with an increased risk of T2DM (Hazard Ratio [HR] 1.87, 95% Confidence Interval [CI] 1.32-2.65). Furthermore, GIP levels showed a stronger predictive value for T2DM development than fasting glucose levels. Conclusion: Elevated GIP levels are an independent predictor of T2DM development in the Spanish population. This finding highlights the potential role of GIP in the pathogenesis of T2DM and suggests that GIP could be a valuable therapeutic target for diabetes prevention.